Host Innate Immune Responses of Ducks Infected with Newcastle Disease Viruses of Different Pathogenicities - Kang, Yinfeng; Li, Yanling; Yuan, Runyu; Feng, Minsha; Xiang, Bin; Sun, Minhua; Li, Yaling; Xie, Peng; Tan, Yangtong; Ren, Tao (Frontiers in Microbiology, 2015)
Though previous studies have identified two strains of duck-origin Newcastle disease virus (NDV) with varying levels of pathogenicity, the relationship between the early-phase host innate immune response and pathogenesis of ducks infected with these strains in the lungs and thymuses remains unclear. In this study, we compared the viral distribution and mRNA expression of immune-related genes in ducks following infection with two NDV strains, Duck/CH/GD/SS/10 (SS-10) and Duck/CH/GD/NH/10 (NH-10). Both NDV strains replicated systemically in tested tissues (i.e., small intestine, cecal tonsils, brain, lung, bursa of Fabricius, thymus, and spleen) and exhibited different biological properties in duck pathogenicity. Real-time quantitative polymerase chain reaction showed that the expression of TLR3, TLR7, RIG-I, MDA5, IL-1β, IL-2, IL-6, IL-8, IFN-alpha, IFN-beta, IFN-gamma in the lungs was significantly greater than in the respective thymus genes during the early post infection stage. However, in the lungs, the expression of TLR3, TLR7, IL-1β, IL-2, IL-8, IFN-alpha, IFN-gamma, and MHC II induced by SS-10 at 72 h post-inoculation (hpi) was less than with NH-10. Furthermore, the expression of IL-6 and IFN-beta in the lungs and thymuses following infection with SS-10 was greater than that with NH-10 at 24 and 48 hpi. These results highlight important differences in host innate immune responses, courses of infection, and pathogenesis following NDV infection. Further studies should work to expand understandings of the molecular mechanisms related to NDV infection.